Prostate Cancer Gleason Score From Biopsy to Radical Surgery: Can Ultrasound Shear Wave Elastography and Multiparametric Magnetic Resonance Imaging Narrow the Gap? - Wei, Cheng; Zhang, Yilong; Zhang, Xinyu; Ageeli, Wael; Szewczyk-Bieda, Magdalena; Serhan, Jonathan; Wilson, Jennifer; Li, Chunhui; Nabi, Ghulam (Frontiers in Oncology, 2021)
Objectives: To investigate the impact of ultrasound shear wave elastography (USWE) and multiparametric magnetic resonance imaging (mpMRI) in predicting a change in biopsy-assigned Gleason Score (GS) after radical surgery for localised prostate cancer (PCa). Method: 212 men opting for laparoscopic radical prostatectomy (LRP) between September 2013 and June 2017 were recruited into this study. All the participants had 12-core transrectal ultrasound (TRUS) biopsies and imaging using USWE and mpMRI before radical surgery. The predictive accuracy for imaging modalities was assessed in relation to upgrading and downgrading of PCa GS between the biopsies and radical prostatectomy using Student’s t test and multivariable logistic regression analyses. A decision analysis curve was constructed assessing impact of nomogram on clinical situations using different thresholds of upgrading probabilities. Results: Most GS 6 disease on biopsies was upgraded on radical surgery (37/42, 88.1%). Major downgrading was seen in GS 8 category of disease (14/35; 37.1%), whereas no alteration was observed in GS 7 on biopsies in most men ((55/75; 73.3%). In univariate analysis, higher preoperative prostate-specific antigen (PSA) (p=0.001), higher prostate specific antigen density (PSAD) (p=0.002), stiffer USWE lesions (p=0.009) and higher prostate imaging-reporting and data system (PIRADS) (p=0.002) on mpMRI were significant predictors of upgrading. In multivariate logistic regression analyses, only PSA (p=0.016) and USWE measured tissue stiffness (p=0.029) showed statistical significance in predicting upgrading. Conclusions: Measurement of tissue stiffness using USWE in clinically localised PCa can predict upgrading of GS and has potential to improve patient management options.